Pelatihan Pegembangan Produk dan Teknik Pemasaran Pada Peternak Lebah Madu Kelulut - Eriawaty, Eriawaty; Rahman, Rahman; Putra, Kharisma Nugraha; Sintani, Dea; Hariansono, Hendry Wahyu (Abimanyu : Jornal of Community Engagement, 2024)
This training activity on product development and marketing techniques for kelulut honey beekeepers aims to increase knowledge and skills for the community, by seeing the enormous potential in the Kereng bengkirai village which can be managed by the surrounding community as a source of income. The method used in this community service activity is participatory. Through an approach that focuses on increasing the role of the community actively in the training process provided. Training techniques are carried out in a variety of ways through lectures, questions and answers, and demonstrations. Data collection techniques are carried out by observation, interviews, and documentation. The results of the training that has been carried out show an increase in community knowledge and skills ranging from the development of beekeeping to marketing the results of honey management from these bees.